Stroke Core Volume Weighs More Than Recanalization Time for Predicting Outcome in Large Vessel Occlusion Recanalized Within 6 h of Symptoms Onset - Ligot, Noemie; Elands, Sophie; Damien, Charlotte; Jodaitis, Lise; Sadeghi Meibodi, Niloufar; Mine, Benjamin; Bonnet, Thomas; Guenego, Adrien; Lubicz, Boris; Naeije, Gilles (Frontiers in Neurology, 2022)
Introduction: Perfusion imaging carries weight on thrombectomy decision-making only after 6 hours of symptoms onset. Pathophysiologically, brain perfusion should matter whatever the elapsed time. We aimed To compare relative contribution of recanalization time and stroke core volume in predicting functional outcome in patients treated by endovascular thrombectomy within 6-hours of stroke-onset. Methods: Consecutive patients presenting between January 2015 and June 2021 with (i) an acute ischaemic stroke due to an anterior proximal occlusion, (ii) a successful thrombectomy (TICI ≥ 2) within 6-hours of symptom-onset and (iii) CT perfusion imaging were included. Core stroke volume was automatically computed using RAPID software. Two linear regression models were built that included in the null hypothesis the pre-treatment NIHSS score and the hypoperfusion volume (Tmax > 6s) as confounding variables and 24 hours post-recanalization NIHSS and 90 days mRS as outcome variables. Time to recanalization was used as covariate in one model and stroke core volume as covariate in the other. Results: From a total of 377 thrombectomies, 94 matched selection criteria. The Model null hypothesis explained 37% of the variability for 24 hours post-recanalization NIHSS and 42% of the variability for 90 days MRS. The core volume as covariate increased outcome variability prediction to 57% and 56% respectively. Time to recanalization as covariate marginally increased outcome variability prediction from 37% and 34% to 40% and 42.6% respectively. Conclusion: Core stroke volume better explains outcome variability than the time to recanalization in anterior large vessel occlusion stroke with successful thrombectomy done within 6 hours of symptoms onset. Still, a large part of outcome variability prediction fails to be explained by the usual predictors.